Disparities in dolutegravir utilisation in children, adolescents and young adults (0–24 years) living with HIV. An analysis of the IeDEA Pediatric West African cohort - Valériane Leroy; Anandi Sheth; Julie Jesson; Jean Jacques Koffi; Antoine Jaquet; François Dabis; Didier Koumavi Ekouevi; Karen Malateste; Olivia Keiser; Lehila Bagnan; Simon Boni; Madeleine Amorissani Folquet; et al. (BMJ Global Health)
Introduction We describe the 24-month incidence of Dolutegravir (DTG)-containing antiretroviral treatment (ART) initiation since its introduction in 2019 in West Africa.Methods We included all patients aged 0–24 years on ART from nine clinics in Côte d’Ivoire (n=4), Ghana, Nigeria, Mali, Benin, and Burkina Faso. Baseline varied by clinic and was defined as date of first DTG prescription; patients were followed up until database closure/death/loss to follow-up (LTFU, no visit ≥7 months), whichever came first. We computed the cumulative incidence function for DTG initiation; associated factors were explored in a shared frailty model, accounting for clinic heterogeneity.Results Since 2019, 3350 patients were included; 47.2% were female; 78.9% had been on ART ≥12 months. Median baseline age was 12.5 years (IQR 8.4–15.8). Median follow-up was 14 months (IQR 7–22). The overall cumulative incidence of DTG initiation reached 22.7% (95% CI 21.3 to 24.2) and 56.4% (95% CI 54.4 to 58.4) at 12 and 24 months, respectively. In univariate analyses, those aged <5 years and female were overall less likely to switch. Adjusted on ART line and available viral load (VL) at baseline, females aged >10 years were less likely to initiate DTG compared with males of the same age (adjusted HR among 10–14 years: 0.62, 95% CI 0.54 to 0.72; among ≥15 years: 0.43, 95% CI 0.36 to 0.50), as were those with detectable VL (>50 copies/mL) compared with those in viral suppression (aHR 0.86, 95% CI 0.77 to 0.97) and those on PIs compared with those on non-nucleoside reverse-transcriptase inhibitors (aHR after 12 months of roll-out: 0.75, 95% CI 0.65 to 0.86).Conclusion Paediatric DTG uptake was incomplete and unequitable in west African settings: DTG use was least likely in children <5 years, females ≥10 years and those with detectable VL. Maintained monitoring and support of treatment practices is required to better ensure universal and equal uptake.